Experimental study on the propulsion performance of a partially submerged propeller - Ha, Jeongsoo; Park, Jongyeol; Park, Gyukpo; Kim, Jaehun; Kim, Jaeheon; Seo, Jeonghwa; Rhee, Shin Hyung (International journal of naval architecture and ocean engineering, 2023)
The present study concerns an open water performance of a partially submerged propeller. To investigate the free surface effects on the propulsion performance, the force and moment were measured, and the ventilation phenomena were visualized with respect to submergence ratios and advance coefficients. The thrust loss in heavy load conditions due to ventilation at the suction side of the propeller blade was observed. The extent of the ring-shaped ventilation phenomena increased as the advance coefficients decreased, resulting in thrust loss. Using the underwater camera and the fast Fourier transform results of the thrust, the ventilation phenomena were classified into five types. Also, the shaft excitation force of the propeller was analyzed. The shaft-bearing load was approximately 100% greater than the propeller weight in the ballast draft condition. A larger load was applied to the shaft due to the movement of the thrust eccentricity near the free surface.